Military-Civilian Collaborations for mTBI Rehabilitation Research in an Active Duty Population: Lessons Learned From the Assessment of Military Multitasking Performance Project. Issue 1 (January 2017) - McCulloch, Karen L.; Cecchini, Amy S.; Radomski, Mary V.; Scherer, Matthew R.; Smith, Laurel; Cleveland, Caroline; McMillan, Henry P.; Davidson, Leslie F.; Weightman, Margaret M.
Abstract : This article describes lessons learned in the planning, development, and administration of a collaborative military-civilian research project, the Assessment of Military Multitasking Performance, which was designed to address a gap in clinical assessment for active duty service members with mild traumatic brain injury who wish to return to active duty. Our team worked over the course of multiple years to develop an assessment for military therapists to address this need. Insights gained through trial and error are shared to provide guidance for civilian researchers who may wish to collaborate with active duty researchers.